Chronic Histological Damage in Early Indication Biopsies Is an Independent Risk Factor for Late Renal Allograft Failure. Issue 1 (8th November 2012) - Naesens, M.; Kuypers, D. R. J.; De Vusser, K.; Vanrenterghem, Y.; Evenepoel, P.; Claes, K.; Bammens, B.; Meijers, B.; Lerut, E.
<x xml:space="preserve">Abstract</x> The impact of early histological lesions of renal allografts on long‐term graft survival remains unclear. We included all renal allograft recipients transplanted at a single center from 1991 to 2001 (N = 1197). All indication biopsies performed within the first year after transplantation were rescored according to the current Banff classification. Mean follow‐up time was 14.8 ± 2.80 years. In multivariate Cox proportional hazards analysis, arteriolar hyalinosis and transplant glomerulopathy were independently associated with death‐censored graft survival, adjusted for baseline demographic covariates. Arteriolar hyalinosis correlated with interstitial fibrosis, tubular atrophy, mesangial matrix increase, vascular intimal thickening and glomerulosclerosis. Clustering of the patients according to these chronic lesions, reflecting the global burden of chronic injury, associated better with long‐term graft survival than each of the chronic lesions separately. Early chronic histological damage was an independent risk factor for late graft loss, irrespective whether a specific, progressive disease was diagnosed or not, while T cell‐mediated rejection did not. We conclude that individual chronic lesions like arteriolar hyalinosis, tubular atrophy, interstitial fibrosis, glomerulosclerosis, mesangial matrix increase and vascular intimal thickening cannot be seen as individual entities. The global burden of early chronic histological damage within the first year after transplantation importantly affects the fate of the allografts.